Procedurally Fair Collective Provision: Its Requirements and Experimental Functionality - Werner Güth; Hartmut Kliemt; Anastasios Koukoumelis; M. Vittoria Levati; Matteo Ploner (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper derives and justifies a procedurally fair bidding mechanism and reviews experiments that apply the mechanism to public projects provision. In the experiments, not all parties benefit from provision, and the projects' costs can be negative. The experimental results indicate that the mechanism is conducive to efficiency, despite the multiplicity of equilibria and underbidding incentives. The only condition is that the cost of the most efficient project must be positive.
Keywords: C72; C92; D63; H44; 330; public project; bidding behavior; procedural fairness